2019
DOI: 10.36076/ppj/2019.22.e315
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Pectoral Nerve Block I and Serratus-Intercostal Plane Block Alleviate Postoperative Pain in Patients Undergoing Modified Radical Mastectomy

Abstract: Background: Simultaneous application of pectoral nerve block and serratus-intercostal plane block (SPB) is one of the most desirable multimodal analgesic strategies, with wide implementation of the enhanced recovery after surgery pathway for modified radical mastectomy (MRM). Objectives: The aim of the present study was to investigate the efficacy and safety of ultrasoundguided pectoral nerve block I (PECS I) and SPB for postoperative analgesia following MRM. Study Design: A randomized, prospective study. Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…13 PECS I combined with SAPB was reported to provide excellent perioperative pain relief following MRM. 14 PECSII block was compared to a placebo block in patients undergoing mastectomy or tumorectomy in a randomized, double-blind study. The authors reported that patients in the PECSII group experienced significantly less pain with less postoperative opioid requirements.…”
Section: Discussionmentioning
confidence: 99%
“…13 PECS I combined with SAPB was reported to provide excellent perioperative pain relief following MRM. 14 PECSII block was compared to a placebo block in patients undergoing mastectomy or tumorectomy in a randomized, double-blind study. The authors reported that patients in the PECSII group experienced significantly less pain with less postoperative opioid requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the remaining 25 full-text publications were carefully evaluated to check their eligibility. Furthermore, 12 trials were eliminated owing to the following reasons: they were case reports ( n = 1) [ 16 ]; SAPB was not the only intervention ( n = 5) [ 17 – 21 ]; they were conference abstracts ( n = 2) [ 10 , 22 ]; and SAPB was compared with other types of nerve blocks ( n = 4) [ 11 , 23 – 25 ]. Eventually, we included 13 eligible and authentic studies [ 12 , 26 – 37 ] in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Regional anesthesia has gained popularity for its opioidsparing strategies. High consumption of opioids can lead to greater pain sensitization and increases the risk of developing sensory disturbances following surgery (19,(25)(26)(27). Interpectoral plane blockade and pectoserratus plane blockade can be employed to obtain blockade of the upper intercostal nerves as well as reduce resting and dynamic pain scores and morphineequivalent consumption.…”
Section: Discussionmentioning
confidence: 99%